Students Perceptions of Podcasts Used for Independent Pronunciation Learning (A Qualitative Study) - Ramawati, Ramawati; Hastini, Hastini; Sadilia, Sukmawati; Mukrim, Mukrim (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to explore students’ perceptions of using podcasts as a medium for independent pronunciation learning and to identify the factors that support and hinder their use. The research employed a qualitative descriptive design involving English Language Education students at Tadulako University. The participants were selected using purposive and snowball sampling techniques, and data were collected through semi-structured interviews. The findings reveal that students generally have positive perceptions of podcasts for independent pronunciation learning. Podcasts are considered easy to use, flexible, and accessible anytime and anywhere, allowing students to practice pronunciation independently and repeatedly. Students also reported that podcasts help them become more familiar with native speakers’ pronunciation, intonation, and accents. However, despite these benefits, several challenges were identified, including the lack of direct practice, limited feedback, and uncertainty about pronunciation accuracy without lecturer guidance. Therefore, while podcasts are effective as a supporting medium for independent pronunciation learning, they should complement, rather than replace, formal classroom instruction. The study suggests that lecturers integrate podcasts into pronunciation teaching while providing guidance and feedback to optimize students’ learning outcomes.